2020
DOI: 10.1024/1661-4747/a000418
|View full text |Cite
|
Sign up to set email alerts
|

Präoperatorisches Denken bei verschiedenen psychischen Störungen: Zwei Querschnittsstudien zum besseren Verständnis des CBASP

Abstract: Zusammenfassung. Hintergrund: In der Behandlung der persistierenden depressiven Störung (PDD) werden Psychotherapien mit interpersonellem Schwerpunkt empfohlen. Ein Beispiel dafür ist das Cognitive Behavioral Analysis System of Psychotherapy (CBASP), was davon ausgeht, dass Menschen mit PDD zu einem präoperatorischen Denkstil neigen. Das Ziel dieser Arbeit ist herauszufinden, ob dieser Denkstil auch bei Menschen mit einer Panikstörung oder einem chronischen Rückenschmerz beobachtet werden kann. Methodik: In ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies using this measure have shown higher levels of preoperational thinking in patients with PD compared to patients with ED or healthy controls (11,18,19). Preoperational thinking was also linked to childhood maltreatment with a mediating effect of interpersonal fears (11), as well as mediating the association of childhood maltreatment and a hostile interpersonal style (20).…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies using this measure have shown higher levels of preoperational thinking in patients with PD compared to patients with ED or healthy controls (11,18,19). Preoperational thinking was also linked to childhood maltreatment with a mediating effect of interpersonal fears (11), as well as mediating the association of childhood maltreatment and a hostile interpersonal style (20).…”
Section: Introductionmentioning
confidence: 85%
“…Patients with depression have been found to exhibit hostile and submissive interpersonal behavior and these behavior patterns are even more pronounced in individuals suffering from PDD (16). This hostile-submissive behavior might be associated with experiences of early emotional abuse (17) and this association might be mediated by a specific deficit in social cognition termed preoperational thinking (17). The term preoperational thinking was originally coined by Piaget's theory of cognitive-affective development (18).…”
Section: Introductionmentioning
confidence: 99%
“…This global and prelogical way of thinking has been summarized in the words of one chronically depressed patient: "Whatever I do, nothing will ever change" (19). Utilizing the Luebeck Questionnaire for Recording Preoperational Thinking (LQPT) as a measure specifically developed to assess preoperational thinking (20), studies found higher levels of preoperational thinking in chronically depressed patients compared to episodically depressed patients and healthy controls (17,(19)(20)(21)(22). Further, preoperational thinking is associated with early emotional abuse and this association might be mediated by interpersonal fears (19).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, indirect evidence for a relationship between impaired social cognition and a hostile and overly submissive interpersonal style has been discussed (26). Furthermore, preoperational thinking appears to mediate the association between adverse childhood experiences and a hostile interpersonal style in depressed patients (28). In particular, it has been shown that early emotional neglect, abuse, and rejection during childhood are important risk factors to interpersonal difficulties in chronic depression (29).…”
Section: Introductionmentioning
confidence: 99%